Perancangan Aplikasi Sistem Informasi Akuntansi Penjualan Berbasis Web (Studi Kasus pada CV. Citra Mandiri) - Fryda Ismawati Nur Azizah; Sudjana Sudjana (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The use of good technology can have a positive impact on the development of the company. Sales accounting information system is one of the application of accounting information system that can help companies whose main activities are sales. Sales are a way for companies to earn revenue. CV. Citra Mandiri is a company that provides building construction services. Within a month, the company conducted service sales transactions 3-4 times, with turnover reaching Rp. 50.000.000. The company still implements a sales accounting information system manually using paper and stationery, and semi-manual using spreadsheet applications. So that recording until the creation of sales reports is not effective and efficient. The company often has difficulty to record and process sales data, as well as losing documents, notes, and files. To overcome this, it is necessary to design a web-based sales accounting information system application. This research is qualitative research using case study approach. This application was developed using SDLC (system development life cycle), CodeIgniter framework and MySQL database management system. In addition, this application is designed to adapt to the current sales accounting information system, starting from input orders by clients, to produce an output in the form of sales-related reports.